PENGARUH PENGGUNAAN LEMBAR KERJA PESERTA DIDIK BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI DAUR BIOGEOKIMIA - Hafifah, Annisa Nur; Purnomo, Aris Rudi (PENSA: E-JURNAL PENDIDIKAN SAINS, 2023)
This research aimed to improve student learning outcomes and describe the implementation of learning and student responses to learning using student worksheets based on Problem based Learning on biogeochemical cycle material. This type of research is pre-experimental design, with the research design used being one group pretest-posttest design. The objectives of this research were 1) to determine the increase in learning outcomes after using Problem based Learning worksheet, 2) to find out the response of students after taking part in learning using Problem based Learning worksheet. Based on the research results, analysis of learning implementation shows that learning implementation is quite effective, the N-Gain obtained a score of 0.54 in the medium category, student responses showed a positive response in the very good category. Based on the results of the paired t-est, the value is <0.05. Shows the influence on student learning outcomes by using Problem based Learning worksheets. Data on student learning outcomes obtained a percentage of learning completeness of 61.65% and increased to 82.96% with the completion criteria. It can be concluded that the use of Problem based Learning worksheet can improve student learning outcomes and be effectively applied in the learning process.